Students’ Perception on Self-Assessment of Writing Competency at Vocational High School - Barus, Lanina Mayrani br; Dewi, Ni Luh Putu Eka Sulistia; Paramartha, Anak Agung Gede Yudha; Wahyuni, Luh Gede Eka (Jurnal Pendidikan Bahasa Inggris undiksha, 2024)
Self-assessment has several advantages in the process of learning English language skills, especially writing skills. This research aims to analyze students' perceptions are and the difficulties they face when implementing self-assessment in improving students' writing skills at Vocational High School. This study uses a survey method with a qualitative approach. The participants of this study consisted of students studying in grades 10 and 11 at Vocational High School. The research collected data using an open-ended questionnaire to gain accurate data on student perceptions. Then, use interviews to find out the challenges faced by students. The interview statements are aligned with the theoretical framework proposed in the questionnaire. The data collected from the questionnaire was analyzed using Excel to get the median result. Thematic analysis was employed to assess the data collected during the interviews. The findings of this study indicate that students have perceptions that tend to be positive towards the application of self-assessment of writing competence as a means for students to reflect on themselves, help students improve the quality of their writing, motivate students to be more independent, and confident, also students can assess and monitor their progress. Students also experience obstacles in carrying out self-assessments, namely limited guidelines, and self-assessment criteria.